Infection of Galleria mellonella (Lepidoptera) Larvae With the Entomopathogenic Fungus Conidiobolus coronatus (Entomophthorales) Induces Apoptosis of Hemocytes and Affects the Concentration of Eicosanoids in the Hemolymph - Wrońska, Anna Katarzyna; Kaczmarek, Agata; Kazek, Michalina; Boguś, Mieczysława Irena (Frontiers in Physiology, 2022)
Apoptosis and autophagy, the mechanisms of programmed cell death, play critical roles in physiological and pathological processes in both vertebrates and invertebrates. Apoptosis is also known to play an important role in the immune response, particularly in the context of entomopathogenic infection. Of the factors influencing the apoptotic process during infection, two of the lesser known groups are caspases and eicosanoids. The aim of this study was to determine whether infection by the entomopathogenic soil fungus Conidiobolus coronatus is associated with apoptosis and changes in caspase activity in the hemocytes of Galleria mellonella larvae, and to confirm whether fungal infection may affect eicosanoid levels in the host. Larvae were exposed for 24 hours to fully-grown and sporulating fungus. Hemolymph was collected either immediately after termination of exposure (F24 group) or 24 hours later (F48 group). Apoptosis/necrosis tests were performed in hemocytes using fluorescence microscopy and flow cytometry, while ELISA tests were used to measure eicosanoid levels. Apoptosis and necrosis occurred to the same degree in F24, but necrosis predominated in F48. Fungal infection resulted in caspase activation, increased PGE1, PGE2, PGA1, PGF2α and 8-iso-PGF2α levels and decreased TXB2 levels, but had no effect on TXA2 or 11-dehydro-TXB2 concentrations. In addition, infected larvae demonstrated significantly increased PLA2 activity, known to be involved in eicosanoid biosynthesis . Our findings indicate that fungal infection simultaneously induces apoptosis in insects and stimulates general caspase activity, and this may be correlated with changes in the concentrations of eicosanoids.